Analytical novel solutions to the fractional optical dynamics in a medium with polynomial law nonlinearity and higher order dispersion with a new local fractional derivative - Yepez-Martinez, H.; Khater, Mostafa M. A.; Rezazadeh, Hadi; İnç, Mustafa (Elsevier, 2021)
Novel solutions for the nonlinear dynamics of Schrodinger equation for polynomial law medium with third-order dispersion (TOD), fourth-order dispersion (FOD), and self-steepening are investigated based in a novel local fractional derivative of order alpha and the Jacobi elliptic function method which are combined into a novel fractional sub-equation method. The Jacobi elliptic function method will provide different types of analytical solutions and not only soliton type solutions for the propagation of ultra-short optical signals through a polynomial law medium. Solutions are illustrated in 3-D graphs, contour plots and 2-D plots under the obtained constraint conditions. (c) 2021 Elsevier B.V. All rights reserved
Keywords: Analytical solutions in medium with polynomial law nonlinearity; Fractional order derivative; Fractional sub-equation method